1999
DOI: 10.1292/jvms.61.649
|View full text |Cite
|
Sign up to set email alerts
|

1, 25-Dihydroxyvitamin D<sub>3</sub>, Recombinant Human Transforming Growth Factor-&beta;<sub>1</sub>, and Recombinant Human Bone Morphogenetic Protein-2 Induce In Vitro Differentiation of Canine Osteosarcoma Cells

Abstract: ABSTRACT. Effects of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), recombinant human transforming growth factor (rhTGF)-β1 and recombinant human bone morphogenetic protein (rhBMP)-2 on differentiation in four different canine osteosarcoma cell lines (POS53B, 53C, 53D and 14A) were examined using markers specifically expressed by phenotypic osteoblasts. 1,25(OH)2D3 increased alkaline phosphatase (ALP) activity in one cell line, osteocalcin production in two lines and type I collagen production in three lines. RhTGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…1B). This model is supported by the following facts: First, OS tumors exhibit the characteristics of undifferentiated osteoblasts [26,75,83,181,195,196,219,233,277]. Second, differentiation-promoting agents (eg, PPARc agonists and 9-cis-retinoic acid) induce osteoblast differentiation [75,76].…”
Section: Possible Links Between Defective Osteogenic Differentiation mentioning
confidence: 98%
“…1B). This model is supported by the following facts: First, OS tumors exhibit the characteristics of undifferentiated osteoblasts [26,75,83,181,195,196,219,233,277]. Second, differentiation-promoting agents (eg, PPARc agonists and 9-cis-retinoic acid) induce osteoblast differentiation [75,76].…”
Section: Possible Links Between Defective Osteogenic Differentiation mentioning
confidence: 98%
“…32 Human OS tumors usually exhibit osteoblast-like features. 3,[33][34][35][36][37][38][39] We demonstrated that differentiation-promoting agents (eg, PPARg agonists and 9-cis retinoic acid) can induce osteoblast differentiation and inhibit OS cell proliferation. 3,40 Here, we investigate whether the disruption of osteoblast differentiation plays a role in OS development.…”
mentioning
confidence: 90%
“…3,4,6,13,14 Other causes of hyperphosphatasemia in adult dogs include increased osteoblastic activity associated with increased bone modeling (or remodeling) and lytic lesions of bone. 4,6,[14][15][16][17][18] Scottish Terriers reportedly have higher ALP activities than do other breeds. 19 It has been suggested that high ALP activity in otherwise healthy Scottish Terriers may possibly be attributable to excessive activity of the bone ALP isoform, which is the mechanism of benign familial hyperphosphatasemia, a rare inherited condition in Siberian Huskies.…”
mentioning
confidence: 99%